Routine prenatal ultrasound anomaly screening program in a Nigerian university hospital: redefining obstetrics practice in a developing African country (2015)
Background: Congenital anomalies are among the leading causes of fetal and infant morbidity and mortality worldwide. Prenatal ultrasound (US) screening has become an essential part of antenatal care in the developed world. Such practice is just evolving in die developing countries such as Nigeria. The aim of this article is to present our initial experience and demonstrate the effectiveness of a prenatal US screening program in detecting congenital malformation in a developing country. Materials and Methods: This was a prospective evaluation of the prenatal .US screenings conducted at a major referral hospital in Southwestern Nigeria All pregnant women referred to the antenatal clinic for mid-trimester screening during the period of study were assessed. Results: Two hundred and eighty-seven pregnant women (5 with twin gestations) were presented for fetal anomaly scan during the study period. Twenty-nine anomalies (9.9%) were detected among the scanned population. Sixteen of the anomalies were followed to delivery/termination with a specificity of 93.5%. The commonest malformations were demonstrated in the genitourinary tract (34.5%) followed by malformations within the central nervous system (27.6%). Six (20.6%) of the anomalies were lethal. Five of the anomalies were surgically collectable. Conclusion: Institutions and hospitals across Nigeria and other low- and middle-income countries need to develop policies and programs that would incorporate a standardized routine screening prenatal US in order to improve feto-maternal well-being and reduce the high perinatal mortality and morbidity in developing nations.